2010
DOI: 10.9773/sosei.51.984
|View full text |Cite
|
Sign up to set email alerts
|

Control of Wall Thickness Distribution by Oblique Shear Spinning Methods

Abstract: A flexible method of forming circumferentially variant wall thickness distributions on the same shape is attempted using two oblique sheet spinning processes. The fundamental strategy entails the inclination of the flange plane of the workpiece during forming. In one type of synchronous dieless spinning, edge-hemmed aluminum blanks of 186 mm diameter and 1.5 mm thickness are formed for truncated cone shells of 30 degrees half-angle, by synchronizing the motion of the spherical head roller in the axial and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In recent years, some other novel spinning processes are also emerged. Sekiguchi et al [46,47] tilted depending on the inclination angle  of the plane and the rotational angle of the spindle. By applying this method, it was predicted that the wall thickness distribution could be varied while retaining the same shape by altering the inclination angle of its flange plane during the process.…”
Section: Longitudinal Tooth Spinningmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some other novel spinning processes are also emerged. Sekiguchi et al [46,47] tilted depending on the inclination angle  of the plane and the rotational angle of the spindle. By applying this method, it was predicted that the wall thickness distribution could be varied while retaining the same shape by altering the inclination angle of its flange plane during the process.…”
Section: Longitudinal Tooth Spinningmentioning
confidence: 99%
“…By applying this method, it was predicted that the wall thickness distribution could be varied while retaining the same shape by altering the inclination angle of its flange plane during the process. The final wall thickness of a conical part was determined by the half-angle, inclination angle and the original thickness of the blank in accordance to the sine law [47]. Therefore this spinning method can be classified as shear spinning.…”
Section: Longitudinal Tooth Spinningmentioning
confidence: 99%
“…The axial distribution of the wall thickness of a product was pointed out to be adjustable in the conventional spinning of metal sheets and the flow forming of metal tubes by Wong et al [4]. However, it is difficult to adjust the circumferential distribution in metal spinning without using a blank of nonuniform thickness or milling after forming [5]. Yoshihara et al [6] controlled the wall thickness of an AZ31-O dome formed from a tube by hot conventional neck spinning through the roller path.…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that from their experiment, the influence of the wall thickness deviation on the workpiece quality was great; it is necessary to control the wall thickness deviation within a certain range, and the wall thickness difference and the section ellipticity were small with the negative deviation rate at 3%. Sekiguchi et al 2012 [5] attempted a flexible method to control the forming circumferentially variant wall thickness distributions on the same shape by using two oblique sheet spinning processes. The wall thickness around circumferential direction was uneven and difficult to control for novel asymmetric and non-circular cross-sectional spinning [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The spinning of "Tripode" and "Pagoda" shape workpiece were simulated by Awiszus and Härtel, then experiments were carried out to verify the simulation results [16]. Sekiguchi and Arai investigated the oblique shear spinning and tried to control the wall thickness distribution after spinning [17]. Zhang et al developed an accurate and effective three-dimensional (3D) FE model to improve the forming qualities of the large ellipsoidal heads formed by power spinning [18].…”
Section: Introductionmentioning
confidence: 99%